Pengaruh Rasio Penambahan Stevia dan Gula Aren Terhadap Karakteristik Kimia Fisik dan Organoleptik Dodol Susudap karakteristik Kimia Fisik Dan Organoleptik Dodol Susu - Kiki Tri Wahendra; Anis Nurhayati (Politeknik Negeri Ketapang, 2025)
Milk dodol is a traditional food made from glutinous rice flour, granulated sugar, palm sugar with a taste that tends to be sweet and has a chewy texture. The high sugar content in milk dodol if consumed excessively can have an impact on body health, such as causing obesity and diabetes. Alternative natural sweeteners stevia can be used to replace granulated sugar in making milk dodol. This study aims to evaluate the effect of the ratio of stevia and palm sugar addition on the physical and organoleptic chemical characteristics of milk dodol with a ratio of stevia (60%, 70%, 80%, 90%, 100%) and palm sugar (40%, 30%, 20%, 10%, 100%). The parameters analyzed include sugar content, water content and organoleptic tests. The results showed that increasing the percentage of stevia had a significant effect on decreasing sugar content and increasing water content. The 80:20 formulation (stevia: palm sugar) was organoleptically very popular in terms of taste and texture. This combination is recommended as a sweet and healthy milk dodol formulation.